Analysis and Comparison of Different Blockchain Algorithms in IoT Security. Issue 1 (January 2021) - Parmar, Monika; Kumar, Neeraj; Kaur, Harsimran Jit; Sharma, Abha; Sharma, Sandhya; Sandhu, Mamatha
Abstract: Internet of things (IoT) and Blockchain are two advancements that are picking up notoriety since the hour of their creation. Sooner rather than later, IoT is going to impact everything we use in our daily lives. As the utilization of this innovation expands, the danger to misuse it likewise increments. Existing advancements are insufficient to manage this. Along these lines, Blockchain has risen as a successful answer for understanding the security issues identified with IoT. Information put away in Blockchain is permanent and can't be changed very effectively. Likewise, the information is added to the block only after it is affirmed by everybody in the system, and in this manner, it is permitting secure exchanges. The individuals who approve the exchanges or transactions and include them in a block are known as miners or excavators. In this article, a detailed overview of the different Blockchain algorithms that are being used for IoT security has been explored. Also, an attempt has been made to provide a detailed overview regarding Blockchain which can act as a reference for the researchers who wish to pursue research in the Blockchain domain.